Effect of Potassium Deficiency Upon Translocation of (14)C in Attached Blades and Entire Plants of Sugarcane - Hartt, Constance E. (1969)
A deficiency in potassium decreased the translocation of labeled photosynthate from the leaf to the rest of the plant. Translocation was inhibited in blades which exhibited no visible symptoms of potassium deficiency and in which no decrease in photosynthesis was detected. In more severe deficiency both the rate of photosynthesis and the conversion of intermediates to end products decreased. The rate of respiration in deficient blades increased. The decrease in translocation caused by potassium deficiency is considered to be a primary effect and not secondary to the development of the well-known symptoms of potassium deficiency.